Metode Altman Z-Score untuk Memprediksi Financial Distress Perusahaan Bidang Konstruksi pada Tahun 2020 -2023 - Dimas Dwi Darmawan; Ujang Suherman; Rengga Madya Pranata (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to use the Altman Z-Score approach analysis to describe the level of corporate bankruptcy. This type of qualitative research uses secondary data from the financial statements of construction companies in 2020–2023. Of the eight companies, 7 companies were selected through purposive sampling. According to the Altman Z-Score analysis, a company is considered healthy if its Z-Score is greater than 2.99; a company that is at risk of bankruptcy and can be saved if its Z-Score is between 1.81 and 2.99; and a company that has a high risk of bankruptcy if its Z-Score is less than 1.8. Based on the results of the study, in the last four years, namely 2020, there were four bankrupt business entities and two business entities entered the gray zone. In 2021, five business entities had good status, while two business entities were categorized as bankrupt. In 2022, there were seven business entities that were classified as healthy. In 2023, there were seven business entities that were classified as healthy. Based on data analysis of construction companies listed on the Indonesia Stock Exchange in 2020, 2021, 2022, and 2023, as many as 70 percent of state-owned companies are bankrupt or are expected to experience financial difficulties. In contrast, as many as 30 percent of non-state-owned companies are expected not to experience financial difficulties.